(untitled) (Eurasian Research Bulletin, 2022)
Сurrently, waste from the molybdenum industry and the production of Almalyk MMC is processed hydrometallurgically to produce ammonium tetramolybdate. Obtaining competitive molybdenum wire is provided under conditions of minimal content of harmful substances, which requires us to pay special attention to the purity of raw materials.